The Role of Genetic Factors in the Differential Invasion Success of Two Spartina Species in China - Li, Feifei; Liu, Xiaoyan; Zhu, Jinfang; Li, Junsheng; Gao, Kexiao; Zhao, Caiyun (Frontiers in Plant Science, 2022)
Biological invasions have become one of the greatest threats to global biodiversity and ecosystem conservation. Most previous studies have revealed how successful invasive species adapt to new environments and climate change through phenotypic and genetic evolution. Some researchers suggested that understanding unsuccessful or less successful biological invasions might be important for understanding the relationships between invasion adaptability and climate factors. We compared the sexual reproduction ability, genetic diversity, and gene × environment interaction in two intentionally introduced alien species in China (Spartina anglica and Spartina alterniflora) based on restriction site-associated DNA (RAD) sequencing. After more than 50 years, the distribution of S. alterniflora has rapidly expanded, while S. anglica has experienced extreme dieback. A total of 212,939 single nucleotide polymorphisms (SNPs) for the two Spartina species were used for analysis. The multilocus genotype (MLG) analysis revealed that clonal reproduction was the prevalent mode of reproduction in both species, indicating that a change in the mode of reproduction was not the key factor enabling successful invasion by Spartina. All genetic diversity indicators (He, Ho, π) in S. alterniflora populations were at least two times higher than those in S. anglica populations, respectively (p < 0.001). Furthermore, the population genetic structure and stronger patterns of climate-associated loci provided support for rapid adaptive evolution in the populations of S. alterniflora in China. Altogether, our results highlight the importance of genetic diversity and local adaptation, which were driven by multiple source populations, in increasing the invasiveness of S. alterniflora.